Zachowania zdrowotne młodzieży w aktualnym kontekście społecznym i ekonomicznym – przegląd wybranych koncepcji - Klimas, Nela (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
The aim of the article is to present opinions regarding the nature of associations between socioeconomic determinants and health behaviours in young people. Furthermore, the attempt to assess the potential of mentioned determinants with regard to school-based health promotion was made. The research material, received from the EBSCO databases, made it possible to examine the impact of socioeconomic status (SES), family, school and peer group on adolescents’ engagement in health-promoting and health compromising behaviours. The findings of the study highlight the important role of SES, school environment, parents’ personal example and their relations with children and school in establishing healthy habits. The influence of peers in leading to health compromising behaviours and gender differences in adapting health behaviors were also indicated.